Effect of Ziziphus Spina-Christi Leaves on the Level of Testosterone Hormone and ‎Semen Parameters of Iraqi Bucks Semen - Faleh, Heba; Dakheel, Mohammed; Quijada, Jessica (The Iraqi Journal of Veterinary Medicine, 2024)
The study aimed to assess the effects of different concentrations of Ziziphus spina-Christi (ZSC) leaves on the fertility of buck goats. Twelve buck goats aged 12–15 months with an average body weight of 22±2 kg were divided randomly into three dietary treatments: T1, T2, and T3, each given a basal diet daily plus feeds of 20 g/kg (2%) of ZSC for T1 and 40 g/kg (4%) of ZSC for ‎T2; and T3 was used as the control that consumed a basal diet only. The experiment lasted for 3 months. On days 45 and 90, blood samples were collected for plasma testosterone measurement using an immunochromatographic assay. Additionally, semen samples were collected at the same time points for physical (volume, color, and pH) and microscopic (semen concentration, mass and individual motility percentage, and live-dead sperm percentages) evaluations. ‎ The results showed that ZSC at 4% significantly (P<0.05) increased the testosterone hormone concentration and all physical parameters at 45 and 90 days comparing to 2% ZSC and control ‎groups. ‎Additionally, ZSC at 4% significantly improved (P<0.05) the microscopic parameters at both ‎time periods compared to 2% ZSC and control groups. The present findings revealed that ZSC at 4% diet could enhance goat semen processing and ‎goat fertility enhanced significantly (P<0.05) the testosterone hormone that had higher values ‎compared to ‎‎(2%) of the ZSC control group. Similarly, (4%) of ZSC affected the physical ‎assessment of ‎semen, such as the volume, color, and pH values. Thus, adding ZSC with a high ‎concentration ‎‎(4%) could enhance goat semen processing and goat fertility in general.